Project financing for a sustainable railways project - Garg, Amit, (SAGE business cases., 2020)
The government is considering a semi-high-speed rail project to tackle some of the current issues associated with the public transportation system in the proposed area. Given the hilly terrain of the area, the current means of transportation are very slow and unreliable. Several studies had shown that the lack of reliable public transport in the proposed area was hindering economic opportunities for several people in the area. Therefore, the government had decided to go ahead with the project.The project is expected to be completed in five years with an expected ridership of around 9 million (both ways) in the initial years. This will increase to 14 million in the next 10 years. The demand would be met by trains with a capacity of 675 passengers per train and the peak hour frequency would be 2 trains per hour (tph). The expected revenue per km would be INR 2.5-3 when traffic starts. Additional revenue of 20% is expected to be generated from the sale of food, water, and other on-board services.The government was considering structuring the entity as a PPP. Among the options for financing the project, green bonds were being considered for some parts of the project. This would ensure a cheap source of finance and also attract ESG investors to the project.